The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1590/2317-1545v39n4172539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutri-priming on germination indices and physiological characteristics of stevia seedling under salinity stress

Abstract: -Poor germination and low seedling growth of stevia (Stevia rebuadiana Bertoni) are common problems in the cultivation of the plant. On the other hand, salinity is one of the abiotic environmental stresses that reduce the performance of the product. The objective in this study was to assess the effect of nutri-priming with selenium (Se), iron (Fe) and boron (B) on stevia seed germination indices and physiological characteristics in sodium chloride (NaCl) salinity condition (0, 30, 60 and 90 mM). Results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 27 publications
3
31
0
Order By: Relevance
“…The application of Se supplementation exhibited no significant effect on chl a and b or carotenoids in sugarcane [ 74 ], in oilseed rape [ 75 ], or in wheat [ 76 ] under control conditions. Stevia seeds primed with sodium selenite, developed seedlings with similar total chlorophyll content to control plants [ 77 ]. The lack of chlorophyll and carotenoid loss in Stevia leaves indicates that the applied Se concentrations were not toxic to the plants [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…The application of Se supplementation exhibited no significant effect on chl a and b or carotenoids in sugarcane [ 74 ], in oilseed rape [ 75 ], or in wheat [ 76 ] under control conditions. Stevia seeds primed with sodium selenite, developed seedlings with similar total chlorophyll content to control plants [ 77 ]. The lack of chlorophyll and carotenoid loss in Stevia leaves indicates that the applied Se concentrations were not toxic to the plants [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen in Table 3, at all drought stress levels, the highest values of GP, GV as well as SL and SVI were noticed in seeds primed by SA + Fe + Zn. The reason of the increment in seedling weight and length as a result of nutri-priming might be due to the role of these elements in increased cell division, cell expansion and meristematic growth, which caused an increase of plant growth (Shahverdi et al, 2017). It has been reported that in the presence of zinc, hormones such as auxin are increased.…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of this element has a remarkable effect on the productivity of photosynthetic organisms (Tewari et al, 2013). Shahverdi et al (2017) reported that stevia seed priming with Fe alone and the integrated application of selenium (Se) and boron (B) significantly increased the total Chl content under salinity stress. In another research, Li and Zhang (2012) concluded that rice seed priming with SA increases the photosynthetic activities in this plant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations